Multicentric Reticulohistiocytosis Presenting with Papulonodular Skin Lesions and Arthritis Mutilans - Raya Saba; Shawn G. Kwatra; Bishwas Upadhyay; Aibek E. Mirrakhimov; Farah N. Khan (Case Reports in Rheumatology)
Multicentric reticulohistiocytosis is a rare multisystem disorder of unknown etiology that is characterized by erosive polyarthritis and papulonodular lesions on the skin, mucous membranes, and internal organs. We report the case of a 54-year-old female who was misdiagnosed as having rheumatoid arthritis and underwent numerous joint replacement surgeries for progressively destructive arthritis in her hands, shoulders, hips, and knees. The patient finally received a diagnosis of multicentric reticulohistiocytosis after histopathological examination of the patient’s left knee arthroplasty which revealed a diffuse histiocytic infiltrate, multinucleated giant cells, and finely granulated eosinophilic cytoplasm with a ground-glass appearance.